PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH BERMUATAN KARAKTER DAN KECERDASAN NATURALIS TERHADAP LITERASI SAINS SISWA - Suhirman Suhirman (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2020)
This study aims to determine the effect of problem based learning models with character emphasis and naturalist intelligence on students' scientific literacy. This study is an experimental research with a treatment design by Level 2 x 2. Learning treatment includes problem-based learning with character emphasis (PBL-CE), and problem-based learning (PBL), each of which is given to groups of students with high naturalist intelligence and low naturalist intelligence. The research sample was two groups of students taken at random at two schools in the city of Mataram, namely Madrasah Aliyah Negeri 2 Mataram and Madrasah Aliyah NW Nurul Jannah Ampenan. The data of student scientific literacy were analyzed descriptive-statistically to get a description of the level of student scientific literacy, as well as the ANOVA test to test the research hypothesis at a significance level of 0.05. The results of this study show that the scientific literacy of students taught with PBL-CE is significantly higher than students taught with PBL, and students with high naturalist intelligence are significantly higher in scientific literacy than students with low naturalist intelligence. Furthermore, the interaction between problem-based learning (PBL-CE and PBL) and naturalist intelligence significantly influences students' scientific literacy.